Analisis Epistemological Obstacle Berdasarkan Kesalahan Menyelesaikan Soal Matematika Materi Eksponen dan Logaritma Siswa MA Plus Nurul Islam Sekarbela - Sri Wahyuningsih; Dedi Riyan Rizaldi; Dewi Sartika; Nilwan; Sripatmi; Ziadatul Fatimah (Action Research Journal, 2024)
This research is based on the large number of students who experience obstacles in solving mathematical problems on exponential and logarithmic materials. The purpose of this study is to describe epistemological obstacles based on errors in solving mathematical problems, exponential materials, and logarithms of grade XA students in MA Plus Nurul Islam. This research method is a qualitative descriptive method with the research subject being class XA students at MA Plus Nurul Islam with a total of 22 students. The data research instruments used are observations, interviews, and tests in the form of descriptions of exponential and logarithmic materials. The data analysis techniques used are: giving tests, analyzing test results, compiling research results and drawing conclusions. The results and discussion of this study are that grade XA students in MA Plus Nurul Islam experience epistemological obstacles. These obstacles consist of: 1). Many students do not understand the concepts of the questions given during the test; 2). Many students make mistakes using calculation operations in answering questions; and 3). Many students make mistakes in writing steps or procedures in answering questions